Strategi Branding Sebagai Upaya Pengembangan Dan Pemasaran Produk UMKM Finza Cake And Cookies - Awwaliya Dhiyaus Syamsiyah; Nurul Azizah (Politeknik Kampar, 2023)
Apart from natural resources, Indonesia also has a variety of manufactured goods and processed foods. Industry in Indonesia is quite good at managing typical Indonesian products, especially food and beverage products. UMKM's participate in the production of traditional processed foods and beverages by using their ideas and creativity, apart from the Indonesian industry. UMKM's are created by an individual, a group of people, or a company that creates products to serve the needs of the surrounding environment. These UMKM's undoubtedly face a number of challenges as they work to manufacture and market their goods. In Probolinggo City, to be precise in Mranggonlawang Village, Dringu District, one of the UMKM's at the KKNT-MBKM group 52 student service center has problems in marketing and product development activities. Planning a marketing strategy to launch UMKM's business activities is the goal of this service activity. The data collection method used is qualitative in nature including interviews, documentation, and observation of UMKM's actors at work. The development of UMKM's products and the success of their marketing efforts are the results of this service activity.